1997
DOI: 10.1021/tx960154l
|View full text |Cite
|
Sign up to set email alerts
|

Peroxy Radical Oxidation of Thymidine

Abstract: The peroxy radical (ROO) is unique among reactive oxygen species implicated in the production of DNA damage in that it possesses an extremely long half-life (order of seconds) and is predicted to have a relatively greater chemical selectivity in its reactions relative to other radical intermediates. Yet no product studies of the reactions of ROO with bases, nucleosides, or DNA have appeared, and thus no meaningful predictions can be made regarding its potential involvement in the production of DNA base damage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 57 publications
2
35
0
Order By: Relevance
“…Significantly, peroxyl radicals are reported to abstract hydrogen atoms from thymine bases and from deoxyribose to form ROOH moieties. 37,38 Such damage sites would serve as plausible sources for OH − desorption under electron impact. Moreover, since it has been observed that radiation-induced radicals in DNA and related molecules, that form and trap at cryogenic temperatures, can combine upon heating, 39 it is interesting to speculate that the decrease in O − signal and increase in OH − desorption observed with increasing film temperature in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Significantly, peroxyl radicals are reported to abstract hydrogen atoms from thymine bases and from deoxyribose to form ROOH moieties. 37,38 Such damage sites would serve as plausible sources for OH − desorption under electron impact. Moreover, since it has been observed that radiation-induced radicals in DNA and related molecules, that form and trap at cryogenic temperatures, can combine upon heating, 39 it is interesting to speculate that the decrease in O − signal and increase in OH − desorption observed with increasing film temperature in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, H 2 O 2 is a potential source for hydroxyl radical (·OH), one of the most dangerous radicals formed through the Fenton reaction in the presence of transition metal ions, as iron. Additionally, azo-initiators like AAPH induce the formation of peroxyl radicals, capable of initiating the chain reaction of lipid peroxidation (Cao et al, 1997;Martini & Termini 1997;Kanno et al, 2003).…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…4B). DISCUSSION fU is one of the major oxidative thymine lesions found in DNA and nucleoside that were exposed to ionizing radiation (44 -46), Fenton-type reactions (46,47), photosensitized reactions (48,49), and peroxy radicals (50). The yield of fU in Fenton-type reactions and ␥-irradiation is comparable to those of 8-oxoG (47) and 5-hydroxypyrimidines (45) that are known as major mutagenic oxidative base lesions (51)(52)(53)(54)(55).…”
Section: Fig 1 Hplc Analysis Of Nucleosides In 25fmentioning
confidence: 98%